Advances in fracture toughness test methods - Glavardanov, Ivan; Gerić, Katarina; Fiši, Juija (Journal of Production Engineering, 1994)
New developments and refinements in fracture toughness rest methods in this paper are deserrbed. To derive COD from the measured clip-gauge displacemen, it is assumed that two halves of a bend or CT speciment rotate about a hinge during the opening of the crack. The location of the hinge in terms of the ligament lenght is given by the rotational factor r. In reality, however, the two halves of specimen and crack faces will bent plastically and/or elasticaly. In this case we may still compute COD measuring clip guage displacment provided that the right value ot r id insertded in relationship.